1988
DOI: 10.1002/stem.5530060304
|View full text |Cite
|
Sign up to set email alerts
|

Effect of recombinant human erythropoietin on the anemia of chronic renal failure

Abstract: Phase I and Phase II studies of recombinant human erythropoietin (rhEpo) were conducted in normal volunteers and in anemic patients with chronic renal failure on maintenance hemodialysis. Three hundred U/person of rhEpo was administered intravenously to healthy normal volunteers in the Phase I study, resulting in no subjective or objective changes. In the Phase II study, 66 patients with chronic renal failure on maintenance hemodialysis with less than 20% hematocrit values were treated with rhEpo in doses of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0
3

Year Published

1989
1989
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 7 publications
(6 reference statements)
2
14
0
3
Order By: Relevance
“…If inhibitors play a significant role, they probably influence the responses caused by rHuEPO administration. It is reported that rHuEPO has been effective in virtually all anemic hemodialysis patients (Winearls et al 1986;Eschbach et al 1987;Bommer et al 1988; Urabe et al 1988;Eschbach 1989). It is known, however, that effectiveness of rHuEPO varies among dialysis patients (Winearls et al 1986;Casati et al 1987;Eschbach et al 1987), and there are a few cases who have resisted to rHuEPO therapy (Kahn et al 1988).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…If inhibitors play a significant role, they probably influence the responses caused by rHuEPO administration. It is reported that rHuEPO has been effective in virtually all anemic hemodialysis patients (Winearls et al 1986;Eschbach et al 1987;Bommer et al 1988; Urabe et al 1988;Eschbach 1989). It is known, however, that effectiveness of rHuEPO varies among dialysis patients (Winearls et al 1986;Casati et al 1987;Eschbach et al 1987), and there are a few cases who have resisted to rHuEPO therapy (Kahn et al 1988).…”
Section: Discussionmentioning
confidence: 99%
“…rHuEPO was administered to 10 patients as maintenance therapy. Except for case 9, preliminary rHuEPO administration had been made as a part of a Phase II study (Urabe et al 1988), and all patients responded well. After a given period of time, rHuEPO therapy was started again.…”
Section: The Administration Of Rhuepomentioning
confidence: 99%
See 1 more Smart Citation
“…Erythropoietin (EPO) is a circulating glyco protein hormone that regulates erythropoiesis, and the efficacy of recombinant human (r-Hu) EPO on chronic renal failure has been estab lished in human clinical studies (1,2) and animal experiments (3). We recently found that r-HuEPO was also effective against the anemia in rats with adjuvant arthritis (AA, 4).…”
Section: Abstract-erythrocytesmentioning
confidence: 99%
“…L'introduzione nella pratica clinica di eritropoietine umane ricombinanti (rHuEPO), prodotte su scala industriale mediante tecniche di ingegneria genetica, è stata una delle più importanti innovazioni terapeutiche nel trattamento dei pazienti in dialisi e dei pazienti con IRC. Infatti, la disponibilità di agenti stimolanti l' eritropoiesi (ESA) ha rivoluzionato le modalità di trattamento dell'anemia dei pazienti con IRC, consentendo di mantenere livelli adeguati di emoglobina (Hb) senza dover ricorrere a trasfusioni di sangue [3][4][5][6][7][8][9][10]. Somministrati in modo personalizzato in base alle caratteristiche del paziente, gli ESA compensano la carenza di eritropoietina e stimolano l' eritropoiesi.…”
Section: Introductionunclassified